The Independent Churches and Proselytism in the Balkans - Milkov, Kostake (Occasional papers on religion in Eastern Europe, 2018)
The emergence of the new churches in the Balkans is a relatively recent phenomenon, and it is mainly connected with the Evangelical wing of Protestantism. Apart from the Congregationalist missions within the Ottoman Empire from the mid-nineteenth century including the Methodists and to a much smaller extent, the Baptists and the Pentecostals., and their spinoffs, mainly resulting from geopolitical shifts post-World War I, most of the Evangelical missionary endeavors on the territory of Former Yugoslavia began after the fall of Communism, These aspects are the focus of my essay, although some of the conclusions are also applicable to the Protestant communities with longer historical presence in the region.